Proceedings of the First International Conference on Health, Social Sciences and Technology (ICoHSST 2020) 2021
DOI: 10.2991/assehr.k.210415.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blood Pressure and Pulse Measurements to Tai Chi Exercise in Hypertensive Patients in East Jakarta

Abstract: Increasing prevalence of hypertension (HT) risk factors and number of uncontrolled blood pressure in hypertensive patient still being the focus in health care, especially in nursing promotive-preventive and rehabilitative care. Complementary and alternative nursing care aims to enhance patient awareness and empowerment in unique ways, for instance Tai Chi as mind-body exercise. This study aimed to compare blood pressure and pulse responses of hypertensive individuals to 60 minutes and 30 minutes Yang style Tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…After practicing, the body feels relaxed and full of spirit [5]. Taijiquan exercise is not affected by time, space, environmental conditions, age, athletic ability, the intensity of the exercise, and the size of the exercise can be controlled by themselves, so taijiquan exercise is easy to promote popularization [6][7]. Taijiquan exercise at home or taijiquan rehearsal in the square can allow older people to exercise their bodies.…”
Section: Introductionmentioning
confidence: 99%
“…After practicing, the body feels relaxed and full of spirit [5]. Taijiquan exercise is not affected by time, space, environmental conditions, age, athletic ability, the intensity of the exercise, and the size of the exercise can be controlled by themselves, so taijiquan exercise is easy to promote popularization [6][7]. Taijiquan exercise at home or taijiquan rehearsal in the square can allow older people to exercise their bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Tai Chi is a traditional Chinese martial art, and numerous studies have demonstrated its unique role in promoting physical fitness [10]. It has shown improvements in various chronic diseases [11] such as breast cancer [12], depression [13], Parkinson's disease [14], high blood sugar levels [15], and hypertension [16]. Song et al [17] investigated the impact of traditional Chinese martial arts on the quality of life (QOL) in patients with primary hypertension and analyzed the effects of qigong, Tai Chi, and five-animal exercises.…”
Section: Introductionmentioning
confidence: 99%